Pupillary Dilation in Research: More than Meets the Eye. (3rd July 2022) - Szpernal, Jacob; Bachman Groth, Jane A.; Wynne, Niamh; Williams, Vesper; Spellecy, Ryan; Thuruthumaly, Catherine; Carroll, Joseph
Abstract: Purpose: Pupil dilation is a commonly used procedure in vision research. While often considered a minimal risk procedure, there is the potential for significant adverse effects. Methods: Currently, there is variance in practices and protocols among researchers and institutions, perhaps due to a lack of guidelines for safe pupil dilation practices in research settings. In this perspective, we explore variables that can increase the potential for adverse effects and provide suggestions to limit their impact. Prior to dilation, an investigator can assess an individual's medical status and drug regimen when deciding upon a mydriatic agent to be used. Results: Assessing the angle through a variety of methods (i.e. penlight test, van Herick slit lamp, optical coherence tomography, gonioscopy) can also prevent inappropriate dilation of pupils with concerning anatomical features. During dilation, an investigator should look to limit the potential of infection and use caution in repeat dosing of dilation-resistant pupils. Conclusions: Post-dilation, an investigator should closely monitor eyes with elevated risk factors and improve an individual's health literacy on angle closure complications. When combined with proper informed consent processes regarding adverse effects, the aforementioned can allow for risk mitigation in studies using pupil dilation.